Предмет: Алгебра, автор: ayanabritly

помогите решить по действиям

Приложения:

Ответы

Автор ответа: Шолпаан
0
     a+2b         a-2b       (a+2b)(a+2b) - (a-2b)(a-2b)    
1) --------- - ----------- = ------------------------------------- =
    a(a-2b)    a(a+2b)          a(a-2b)(a+2b)   

   a²+4ab+4b²-a²+4ab-4b²             8ab
= ------------------------------- = ------------------
         a(a-2b)(a+2b)              a(a-2b)(a+2b)

           8ab            a²            8a²b
2) ------------------ * --- = -------------------
    a(a-2b)(a+2b)    1     a(a-2b)(a+2b)
Автор ответа: Шолпаан
0
выручила* ) ага)
Похожие вопросы